2019
DOI: 10.3390/en12163091
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating the Impacts of Covert Cyber Attacks in Smart Grids Via Reconstruction of Measurement Data Utilizing Deep Denoising Autoencoders

Abstract: As one of the most diversified cyber-physical systems, the smart grid has become more decumbent to cyber vulnerabilities. An intelligently crafted, covert, data-integrity assault can insert biased values into the measurements collected by a sensor network, to elude the bad data detector in the state estimator, resulting in fallacious control decisions. Thus, such an attack can compromise the secure and reliable operations of smart grids, leading to power network disruptions, economic loss, or a combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Their methods were tested in IEEE-14, IEEE-57 and IEEE-118 bus standard system, and compared mutually. Ahmed et al in (198) suggested a model to recreate sensorcollected power network measurement data by eliminating the impacts of the hidden information-integrity attack. The model is utlized by a denoising autoencoder, which learns from the data about robust nonlinear representations to root out the bias that a smart attacker has added to the sensor measurements.The scheme was evaluated utilizing standard IEEE 14-bus, 39-bus, 57bus, and 118-bus systems.…”
Section: Auto Encodersmentioning
confidence: 99%
“…Their methods were tested in IEEE-14, IEEE-57 and IEEE-118 bus standard system, and compared mutually. Ahmed et al in (198) suggested a model to recreate sensorcollected power network measurement data by eliminating the impacts of the hidden information-integrity attack. The model is utlized by a denoising autoencoder, which learns from the data about robust nonlinear representations to root out the bias that a smart attacker has added to the sensor measurements.The scheme was evaluated utilizing standard IEEE 14-bus, 39-bus, 57bus, and 118-bus systems.…”
Section: Auto Encodersmentioning
confidence: 99%
“…In addition, this research proposed a method of minimizing the influence of noise and deriving high performance by appropriately refining data from an unbalanced dataset using the methodology of Few-shot learning. Ahmed et al [18] proposed filtering normal data using AutoEncoder to detect and remove noise data present in a dataset in an industrial control environment. This study detects noise data and intentionally changes it into a shape similar to normal data, thereby minimizing data loss and reducing the influence of noise data.…”
Section: Machine Learning Based Anomaly Detection and Data Noise Redu...mentioning
confidence: 99%
“…The proposed framework was used for unsupervised feature learning in complex security scenarios. Deep denoising autoencoders were used to propose a reconstruction scheme to mitigate the impact of covert cyber-attacks in smart grids (Ahmed et al, 2019). The results identified a low error ratio, compared to other schemes.…”
Section: Dataset Technique Referencementioning
confidence: 99%